PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL ROLE PLAYING DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SD N 20 AIR CAMAR KOTA PADANG - Ramadani, Asyifa; Muhammadi, Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the gap between expectations and reality in learning. The reality that was found had not been achieved the expected competencies from student learning outcomes both in terms of attitudes, knowledge and skills. This research aims to describe the improvement in student learning outcomes using a cooperative Role Playing type approach in class V at SDN 20 Air Camar, Padang City. This research is classroom action research (PTK) which uses qualitative and quantitative approaches. Implemented in two cycles, with three meetings covering four stages, namely planning, implementation, observation and reflection. The data collection techniques used are observation, tests and test numbers. The research subjects were 29 teachers and students. Research data was obtained from the assessment of learning implementation plans, implementation processes and learning outcomes. The results of research from the first cycle of the teaching module aspect obtained an average of 87.45% (B), increasing in cycle II to 95.8% (SB). The implementation of cycle I in the teacher activity aspect obtained an average of 86.35% (B) and increased in cycle II to 95.4% (SB). The implementation of cycle I in the student activity aspect obtained an average of 86.35% (B) and increased in cycle II to 95.4% (SB). The learning outcomes of students in cycle I obtained an average of 74.03% (C), increasing in cycle II to 85.65% (B). It can be concluded that the Role Playing model can improve learning outcomes for Pancasila education in elementary schools.